Lecturer Competency Development Model in Designing a Line Learning Resources in University of Muhammadiyah Sumatera Utara - Prasetia, Indra; Akrim, Akrim; Pratiwi, Sri Nurabdiah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to produce a model for developing lecturer abilities (training model) in designing online learning. With the existence of this lecturer capability development model, later the UMSU and the lecturers can easily design and implement an online integrated learning system (SPTD) effectively. The results of this study indicate that the development of lecturer competence in designing online learning resources can improve the quality of human resources that support SPTD at UMSU. The result of this research is a prototype of an open online training program that gives lecturers the ability to design SPTD through the following materials: online learning design, introduction to OER, steps to carry out instructional analysis to obtain competency maps and an outline of an online learning program (GBPP) containing ready-to-use teaching objects. uploaded to the appropriate platform, as well as teaching materials in the form of modules. Teaching objects are in the form of learning programs in various forms such as text, presentations, learning modules, videos, animation, part or all of the subjects/ courses / training subjects, which are ready to be uploaded/ uploaded to various SPTD platforms.